2010
DOI: 10.1093/ejo/cjp151
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of canine transmigration and tooth impaction in a Turkish subpopulation

Abstract: The purpose of this study was to determine the incidence of transmigrated maxillary and mandibular canine teeth and also of the other impacted teeth in a Turkish subpopulation. Five thousand consecutive panoramic radiographs taken of patients who attended the Department of Oral Diagnosis and Radiology, Selcuk University, for routine examination between 2005 and 2007 were examined to identify incidences of transmigrated and impacted teeth. Demographic information of all patients was also recorded. Transmigratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
5
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 17 publications
12
73
5
11
Order By: Relevance
“…In this study, there was a slight overall female predominance, with a male to female ratio of 1:1.41. Although this finding corroborates with most reports, (2,7,12) the sex distribution reported by some authors (17) showed a higher frequency among males. The classification based on the migration pattern and final position of mandibulary canine transmigrants was asserted by Mupparapu (10): Type 1 for a canine impacted mesio-angularly across the midline, labial or lingual to the anterior teeth; Type 2 for a canine horizontally impacted near the inferior border of the mandible inferior to the apices of the incisors; Type 3 for a canine erupting on the opposite side of the jaw; Type 4 for a canine horizontally impacted near the inferior border of the contralateral side and Type 5 regardless of eruption status, canine positioned vertically in the midline with the long axis of the tooth crossing the midline.…”
Section: References With Links To Crossref -Doisupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, there was a slight overall female predominance, with a male to female ratio of 1:1.41. Although this finding corroborates with most reports, (2,7,12) the sex distribution reported by some authors (17) showed a higher frequency among males. The classification based on the migration pattern and final position of mandibulary canine transmigrants was asserted by Mupparapu (10): Type 1 for a canine impacted mesio-angularly across the midline, labial or lingual to the anterior teeth; Type 2 for a canine horizontally impacted near the inferior border of the mandible inferior to the apices of the incisors; Type 3 for a canine erupting on the opposite side of the jaw; Type 4 for a canine horizontally impacted near the inferior border of the contralateral side and Type 5 regardless of eruption status, canine positioned vertically in the midline with the long axis of the tooth crossing the midline.…”
Section: References With Links To Crossref -Doisupporting
confidence: 93%
“…They can appear at any age and ranged from 8 to 62 years (4). Many authors (5)(6)(7) are concerned with the classification and the incidence of impacted teeth, specifically premolars, and the decreasing ratio of canine and lateral teeth. Although failure of eruption of the mandibulary canine and lateral is an unusual event, impaction of the mandibular second premolar is most often seen, accounting for 23% of all impactions excluding third molars, with an overall frequency of impaction of 0.1% (5).…”
Section: Introductionmentioning
confidence: 99%
“…Although this definition finds support [9], it has been also suggested that it is not the distance of migration that is important, but rather the tendency of canines to cross the midline [10]. Some authors have defined the statistical frequency of canine transmigration [2,8,11,12], which ranges from 0.1% [8] to 0.34% [12]. Mupparapu [13] reviewed the literature and classified the transmigrant mandibular canines as ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al 6 scanned 7886 patients and found the transmigration rates as 0.1% for mandibular canines. Aktan et al 29 studied in a Turkish population and their results indicated 0.34% mandibular and 0.14% maxillary TCs. In our study, we found the total transmigration rate as 0.08%.…”
Section: Discussionmentioning
confidence: 96%